Comparison of Agility, Vertical Jump and Speed Parameters in Children Between 6-12 Years - Yeliz Doğru (Türk Spor ve Egzersiz Dergisi)
ABSTRACTThe aim of the study is to compare the agility, vertical jump and velocity parameters in children between 6-12 years of age. One hundred thirty-six children (61 girls, 74 boys) participated as volunteers. The t-test was applied to the participants as a measure of agility test. Vertical jump and 20 meters speed test were applied. Statistics were performed using by SPSS package program. The data were evaluated by the Shapiro-Wilk test for normal distribution. Mann Whitney U test was used for intergroup comparisons. Accordingly, there is a significant difference in favor of males in the vertical jump in the 10-year age group (p lt;0.05). There is a significant difference between males and females in the 9 and 10 age groups in favor of males in vertical jump and speed (p lt;0.05). There was no statistically significant difference in the agility test, but the data showed that men performed better.